RANCANG BANGUN APLIKASI SIMULASI TES TOEFL BERBASIS WEBSITE (STUDI KASUS: PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS MATARAM) - Astuti, Yuli Yana; Anjarwani, Sri Endang; Irmawati, Budi (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2024)
One measure of a person's English proficiency can be seen from the TOEFL test scores obtained. TOEFL (Test of English as a Foreign Language) is a test used to measure a person's English proficiency. If the TOEFL test score has reached a predetermined standard, it can be used for various selection requirements, such as scholarships and college graduation requirements. Based on the regulation of the Chancellor of the University of Mataram Number 7 of 2021 Article 17 Paragraph 8 Letter g, students who wish to conduct a thesis trial need to attach a certificate of completion of the TOEFL test first as proof that the student has indeed taken the TOEFL test and passed the score determined by the program. respective studies or majors, including the Informatics Engineering Study Program. So that in this study the authors will design and build a website based TOEFL test simulation application at the Informatics Engineering Department, University of Mataram. This study uses the CodeIgniter (CI) framework and the personal extreme programming (PXP) system development method. Testing on this application uses the black box testing method and the Mean Opinion Score (MOS). The result is that the application can run properly according to its respective functionality and get a MOS value of 4.6 where this value shows that the TOEFL test simulation application has good quality to use.